EXPLORING THE INTERACTIVE MEDIA: ENHANCING UNDERSTANDING OF QURAN AND HADITH LEARNING THROUGH QUIZIZZ MEDIA IN MADRASAH ALIYAH NEGERI 2 BLITAR - Achmadin, Balya Ziaulhaq; Nabilah, Nafa (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Interactive learning has become a major focus in modern Islamic education. In this context, this research aims to investigate the use of Quizizz media in Al-Qur'an and hadith education at Madrasah Aliyah Negeri 2 Blitar. This research uses a research and development approach to develop and test the effectiveness of Quizizz-based learning in increasing students' understanding of the Al-Qur'an and hadith. The research subjects consisted of class XI students at Madrasah Aliyah Negeri 2 Blitar in the religious class. Research methods include needs analysis, learning design, developing Quizizz-based learning materials, testing, and evaluation. Research data was obtained through comprehension tests and in-depth interviews with students regarding the use of Quizizz in learning the Qur'an and hadith. The collected data was analyzed qualitatively. The research results show that the use of Quizizz media significantly increases students' understanding of the Al-Qur'an and hadith. Apart from that, students showed a positive response to the use of Quizizz in learning the Al-Qur’an and hadith. They consider Quizizz to be an interactive, interesting, and effective tool for studying religious material. This research concludes that the use of Quizizz media can be an effective alternative in improving the learning of the Al-Qur'an and hadith in Madrasah Aliyah Negeri. Therefore, it is recommended that teachers integrate Quizizz into their learning strategies to encourage student participation and understanding of the Al-Qur’an and hadith. Further research can also be conducted to explore the use of Quizizz media in a broader religious education context.